Empowering Adult Inmates with Communication Needs in an East Malaysia Prison - Junaidah Januin; Veronica Petrus Atin; Wan Hurani Osman; Mohd Azri Ibrahim; Halina Sendera Mohd Yakin; Mohd Aqmal Hafidz; Sabariah Abd Rahim; Nor Dawirah Abdul Rahman (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
Communication skills are essential in our daily life because we communicate to pass information from one person to another. However, to have effective communication in a correctional environment, like prisons, is not easy. There are many distractions and barriers to communicate effectively in prisons. Although prison education should be seen as a way to educate inmates to successfully integrate in society upon their release, inmates face difficulties in getting enough reading materials, content and learning tools to enhance their communication skills. This may negatively affect their integration in society and employability after serving their sentences. Therefore, this study aimed to elicit the communication needs of the adult inmates in one of the local prisons in East Malaysia. We employed a textography research approach, where we combined textual analysis and an ethnographic method (interview), to investigate contexts, texts and practices of the prison studied. The findings showed that the inmates need to learn verbal and non-verbal communication, new technologies for communication and simple English conversations. This study is pertinent in providing insights for the development of suitable teaching and learning modules for prison learning institutions.